(untitled) (Experimental biology, 2009)
The results of studying the frequency and spectrum of stable chromosome aberrations induced by different doses of γ-radiation and in the process of adaptive response. Also, peculiarities of changing the frequency of stable and unstable aberrations in long-term cultivation of "young" and "old" lymphocytes in human blood irradiated small and large doses of γ-radiation.